Pentingnya penggunaan garam yodium untuk mengatasi anak pendek - Ampera Miko (Jurnal SAGO Gizi dan Kesehatan, 2020)
Background: One of the nutritional problems in Indonesia is iodine deficiency which can cause IDD. Lack of iodine can result in mumps and cretin, mental retardation, birth defects, children who are less intelligent, and miscarriage in pregnant women. The community is expected to understand the effects of iodine deficiency and excess on health, so it is expected to reduce the number of sufferers of iodine deficiency and excess in Indonesia.Objective: The research aims to improve the behavior of mothers in using iodized salt towards the anticipation of short children. Methods: The study design was quasi-experimental, which was conducted on 30 housewives who had toddlers. The study was conducted from August to September 2018 in Lhoknga District. Pretest and posttest data related to behavior (knowledge, attitudes, and actions) were collected through interviews using a questionnaire. Data processing includes the stages of editing, coding, entry, and tabulating. Data analysis was performed bivariate, using t-dependent tests at 95% CI.Results: This study has shown that there is a significant difference (p= 0.000) between knowledge, attitudes, and actions of mothers before training and after training on the use of iodized salt in the household.Conclusion: The provision of educational training on the use of iodized salt through leaflet media apparently has a statistically significant effect